1998
DOI: 10.1051/rnd:19980410
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of zinc intestinal absorption and reduction of zinc/iron interaction using metal bound to the caseinophosphopeptide 1-25 of β-casein

Abstract: -Binding zinc (Zn)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The effect was attributed to the presence of calcium and partly also casein, which behaved as inhibitors, and the absence of iron enhancers in the product (Toxqui et al, 2013). Zinc in excess has also been reported to reduce iron absorption, and vice versa, an interaction that may be particularly relevant in pregnancy and infancy (Iyengar, Pullakhandam, & Nair, 2010;Pérès et al, 1998).…”
Section: Inhibitorsmentioning
confidence: 99%
“…The effect was attributed to the presence of calcium and partly also casein, which behaved as inhibitors, and the absence of iron enhancers in the product (Toxqui et al, 2013). Zinc in excess has also been reported to reduce iron absorption, and vice versa, an interaction that may be particularly relevant in pregnancy and infancy (Iyengar, Pullakhandam, & Nair, 2010;Pérès et al, 1998).…”
Section: Inhibitorsmentioning
confidence: 99%
“…Among bovine caseins, the second most abundant is ␤-CN, which contains the unique cluster sequence SpSpSpEE near C-terminal extreme (residues 17-21) and the fragment ␤-CN(1-25)4P. Several in vitro assays with tumour cells HT-29 (Ferraretto et al, 2001;Ferraretto et al, 2003) and in vivo studies in rats (Aït-Oukhatar et al, 1997;Aït-Oukhatar et al, 2002;Bouhallab et al, 2002;Pérès et al, 1998Pérès et al, , 1999 have demonstrated that this fragment enhances calcium, iron and zinc absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Fe complexed CPP prevents the formation of poorly absorbed high molecular weight ferric hydroxides. Zinc absorption can also be enhanced by the formation of Zn complexed to CCP, in particular to -CN (f1-25)4P [51]. Some portion of the mineral complexed CPP formed in the small intestine was resistant to the digestive and enteric bacteria enzymes and found in the feces of rats fed a casein-based diet [52].…”
Section: Bioactive Peptides Released In Vitro By the Hydrolysis Of MImentioning
confidence: 99%